Respon Pertumbuhan Tanaman Padi Terhadap Beberapa Rekomendasi Pemupukan Hasil Litbang Pertanian - Syahri Syahri; Renny Utami Somantri (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2013)
Indonensian Agency for Agricultural Research and Development (IAARD) has issued some fertilization recommendations, such as fertilization based on Soil Test Kit for Low Land Rice (PUTS) and Planting Calendar (PC). The reasearch aimed to introduce and examine the effects of various fertilizer recommendations, especially on low land. The research was conducted in Lubuk Sakti village, Indralaya sub-district, Ogan Ilir district from April to Agustus 2013. The research was arranged in 3 treatments fertilization based on PUTS, Â PC and farmer practice (control). The rice varieties used Inpari 12. Legowo plating system was applied by 4:1 (plant spacing 25 x 50 x 12.5 cm) and farmers practice (plant spacing 25 x 25 cm). The plot size was 13 m x 27.5 m. The results showed that both of fertilizer recommendations issued by IAARD were able to increase rice productivity than control.Â STK, PC and control with the yield 5.60 t/ha, 6.56 t/ha and 5,20 t/ha, respectively. Fertilizer recommendations also reduced rice pests and diseases.